Extracts of Papaya Leaf And Castor Seed Potential as Insecticides Against Crocidolomia Pavonana (Lepidoptera: Pyralidae) on Broccoli - Muhammad Sayuthi; Hasnah Hasnah; Saudahrul Jannah (Universitas Syiah Kuala, 2014)
Crocidolomia binotalis is the main pest on broccoli by feeding the leaves causing damage by 100% (Dono Rismanto, 2008). This research was conducted at the Laboratory of Plant Pests Department of Agrotechnology Faculty of Agriculture Univerrsity of Syiah Kuala Banda Aceh from January to December 2014. The aim was to investigate the effectiveness of mixture of extract of papaya leaf and castor beans on mortality of C. pavonana mortality. The study used completely randomized design (CRD). The results showed that the mortality of larvae has reached up to 90 % and feeding inhibition was 91.04%, decrease in the pupae stage 56.67% and imago 46.67% compared to other lower treatments.